Data-constrained assessment of ocean circulation changes since the middle Miocene in an Earth system model - K. A. Crichton; A. Ridgwell; D. J. Lunt; A. Farnsworth; P. N. Pearson (Climate of the Past, 2021)
Since the middle Miocene (15 Ma, million years ago), the Earth's climate has undergone a long-term cooling trend, characterised by a reduction in ocean temperatures of up to 7–8 ∘ C . The causes of this cooling are primarily thought to be due to tectonic plate movements driving changes in large-scale ocean circulation patterns, and hence heat redistribution, in conjunction with a drop in atmospheric greenhouse gas forcing (and attendant ice-sheet growth and feedback). In this study, we assess the potential to constrain the evolving patterns of global ocean circulation and cooling over the last 15 Ma by assimilating a variety of marine sediment proxy data in an Earth system model. We do this by first compiling surface and benthic ocean temperature and benthic carbon-13 ( δ 13 C ) data in a series of seven time slices spaced at approximately 2.5 Myr intervals. We then pair this with a corresponding series of tectonic and climate boundary condition reconstructions in the cGENIE (“muffin” release) Earth system model, including alternative possibilities for an open vs. closed Central American Seaway (CAS) from 10 Ma onwards. In the cGENIE model, we explore uncertainty in greenhouse gas forcing and the magnitude of North Pacific to North Atlantic salinity flux adjustment required in the model to create an Atlantic Meridional Overturning Circulation (AMOC) of a specific strength, via a series of 12 (one for each tectonic reconstruction) 2D parameter ensembles. Each ensemble member is then tested against the observed global temperature and benthic δ 13 C patterns. We identify that a relatively high CO 2 equivalent forcing of 1120 ppm is required at 15 Ma in cGENIE to reproduce proxy temperature estimates in the model, noting that this CO 2 forcing is dependent on the cGENIE model's climate sensitivity and that it incorporates the effects of all greenhouse gases. We find that reproducing the observed long-term cooling trend requires a progressively declining greenhouse gas forcing in the model. In parallel to this, the ...